Research in Environmental Education and Sustainable Development: an overview of publications in Brazilian journals of Qualis A2 - Pezarini, Agnaldo Ronie; Elias, Izilda Guedes; Amaral, Profa. Dra. Carmem Lúcia Costa (Technium Social Sciences Journal, 2021)
This article aims to present an overview of the research in Environmental Education and Sustainable Development in Brazil with four Qualis A2 journals as a locus. From the information obtained in the research locus was constructed a State of the Art and, later, the material obtained, an amount above forty-eight surveys, was analyzed in the light of Bardin. The analysis proceeded in the following categories: Year of publication; Institution of Higher Education; Empirical or Theoretical Work; Instrument of data collection; Area or discipline involved in the research; Objective of the Research; Achievement achieved with Environmental Education and/or Sustainable Development and Classification of work in EE and / or DS. The results obtained in the analysis indicate that the academic production for this subject has presented an increasing and that its discussions are based on multiple biases. We therefore point out the need to conduct studies, including to obtain more data, in order to better characterize the research carried out in the area of ??Environmental Education.